Prognostic Value of the Systemic Inflammation Response Index in Patients with Adenocarcinoma of the Oesophagogastric Junction: A Propensity Score-Matched Analysis. (4th November 2019) - Chen, Yuan; Jin, Ming; Shao, Yingjie; Xu, Guoping
Abstract : Systemic inflammation is closely related to the occurrence and development of tumours. Based on preoperative neutrophil, monocyte, and lymphocyte counts, a new systemic inflammation response index (SIRI) was established, and the predictive ability of the SIRI for the survival of patients with adenocarcinoma of the oesophagogastric junction (AEG) was evaluated by propensity score matching (PSM) analysis. A total of 302 AEG patients undergoing radical surgery were studied. Univariate and multivariate analyses were performed using Cox proportional hazards regression models. Time-dependent receiver operating characteristic (ROC) curves were used to compare the predictive capabilities of the SIRI. PSM was implemented to balance the baseline characteristics. The results showed that the SIRI, PLR, NLR, and MLR were associated with overall survival (OS) in AEG patients based on the Kaplan-Meier survival analysis. Multivariate analysis demonstrated that the SIRI was an independent prognostic factor. The AUC for the SIRI was significantly greater than that for the NLR, PLR, and MLR in predicting the 3- and 5-year OS of AEG patients. In PSM analysis, the SIRI remained an independent prognostic indicator of OS in AEG patients. The SIRI is a novel, simple, and inexpensive prognostic predictor for AEG. The prognostic value of the SIRI is superior to that of the PLR, NLR, and MLR. The SIRI can be used to distinguish the prognosis of AEG patients with different TNM stages and can be an important supplement to TNM staging.